Analysis of the Effects of Role Overload and Role Conflict on Performance through Job Stress as a Mediating Variable in the Cellular Phone Trading Centers in Surabaya - Eddy Madiono Sutanto; Ferdyanto Kurniawan Wiyono (Journal of Economics, Business, and Accountancy Ventura, 2016)
The purpose of this research is to identify the effects Â of the role overload and role conflict on job performance with job stress as mediating variable in the cellular-phone trade-centers. The population consists of the employees working in cellular phone-shops in Trade Centers located in Surabaya, East Java. By using purposive sampling, the characteristics of 316 were selected based on their aged such as over 17 years old, residing in Surabaya, and working the cellular phone traded centers in Surabaya. Â The data were analyzed multiple regression. It was found that the role overload and role conflict have positive effects on job stress. However, the role overload, role conflict, and job stress have negative effects on job performance. Finally, the role overload and role conflict also have effect on job performance through job stress as a mediating variable.